Characterization and protective activity of monoclonal antibodies directed against Fe (3+) ABC transporter substrate-binding protein of Glaesserella parasuis - Kexin Zhu; Dong Yu; Jiahui An; Yufeng Li (Veterinary Research, 2021)
Abstract Glässer’s disease is caused by the agent Glaesserella parasuis and is difficult to prevent and control. Candidate screening for subunit vaccines contributes to the prevention of this disease. Therefore, in this study, the inactivated G. parasuis reference serovar 5 strain (G. parasuis-5) was used to generate specific monoclonal antibodies (mAbs) to screen subunit vaccine candidates. Six mAbs (1A12, 3E3, 4C6, 2D1, 3E6, and 4B2) were screened, and they all reacted with the G. parasuis serovar 5 strain according to laser confocal microscopy and flow cytometry (FCM). Indirect enzyme-linked immunosorbent assay (ELISA) showed that one mAb 2D1, can react with all 15 reference serovars of G. parasuis. Protein mass spectrometry and Western blot analysis demonstrated that mAb 2D1 specifically reacts with Fe (3+) ABC transporter substrate-binding protein. A complement killing assay found that the colony numbers of bacteria were significantly reduced in the G. parasuis-5 group incubated with mAb 2D1 (p < 0.01) in comparison with the control group. Opsonophagocytic assays demonstrated that mAb 2D1 significantly enhanced the phagocytosis of 3D4/21 cells by G. parasuis (p < 0.05). RAW264.7 cells with stronger phagocytic ability were also used for the opsonophagocytic assay, and the difference was highly significant (p < 0.01). Passive immunization of mice revealed that mAb 2D1 can eliminate the bacteria in the blood and provide protection against G. parasuis-5. Our study found one mAb that can be used to prevent and control G. parasuis infection in vivo and in vitro, which may suggest that Fe (3+) ABC transporter substrate-binding protein is an immunodominant antigen and a promising candidate for subunit vaccine development.